CULTURE SHOCK EXPERIENCED BY FOREIGN STUDENTS IN MAKASSAR - Aspan, Muhammad Ikramullah; Nur, Serliah; Syukur, Helmi (Journal of Islamic Culture and Literature (JICeL), 2025)
This research discussed about Culture Shock Experienced by Foreign Students in A Case Study in Makassar. The aim of this research is to find out the steps of culture shock according to Oberg and extended by Gullahorn & Gullahorn (1963), experienced by Foreign Students in Makassar. This research used the qualitative method. In collecting data, the researchers used the interviews as an instrument of the research with four respondents who have been staying in Makassar. The researchers found that there are six processes of culture shock experienced by foreign students. Such as the honeymoon phase, culture shock, recovery phase, adjustment phase, honeymoon at home, and the last reverse culture shock. The result of this research showed that two foreign students could complete four stages of culture shock and the rest of the students showed that they could complete six stages of culture shock. Keywords: Culture Shock, Foreign Students, process, experienced.